TINGKAT PENGETAHUAN MASYARAKAT TENTANG AUTOPSI FORENSIK DI KECAMATAN SIHAPAS BARUMUN KABUPATEN PADANG LAWAS - RUDI ISKANDAR HASIBUAN; MISTAR RITONGA (JURNAL ILMIAH SIMANTEK, 2021)
Cases of unnatural deaths in Indonesia are often unsolved. To reveal those cases forensic autopsy is required, however thisprocedure is often being rejected by the public. To determine the level of public knowledge about forensic autopsy in SihapasBarumun Subdistrict, Padang Lawas Regency. This study is a descriptive study with a cross-sectional approach.The number of samples are 97 people, the calculation was done using Slovin formula, with simple random samplingtechnique. The data were acquired using questionnaires, and processed using SPSS. The overall level of public knowledgeabout forensic autopsy in Sihapas Barumun sub-district, Padang lawas district, are: good 4 people (4.1%), moderate 1person (1.8%), and poor 92 people ( 93.7%). Number of respondents with good knowledge on each categories are: malegender is 3 people (5.88%), age 18-29 years 2 people (6.9%), and based on Bachelor education are 3 people (33.3%).The level of public knowledge about forensic autopsy in Sihapas Barumun District, Padang Lawas Regency is poor.